Construction of Temporary Shelters as A Relief from the Impact of Cyclone Senyar Disaster in the Framework of Settlement Renewal in South Tapanuli Regency, North Sumatra Province - Suangro Lambok H.Stanggang; Ruth Riah Ate Tarigan; Feby Milane (PT. Publikasiku Academic Solution, 2026)
Disaster risk has become an increasingly critical global issue due to the rising frequency and intensity of climate-related hazards, particularly tropical cyclones, which significantly impact vulnerable settlements worldwide. In Indonesia, a disaster-prone archipelagic nation, Cyclone Senyar caused severe damage in South Tapanuli Regency, North Sumatra, resulting in extensive destruction of housing and the displacement of communities. This study aims to analyse the role of Temporary Housing (Hunian Sementara/HUNTARA) in post-disaster recovery and its contribution to settlement rejuvenation in the affected region. The research employs a qualitative case study approach supported by SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and IFAS–EFAS matrix evaluation. Data were collected through in-depth interviews, field observations, and document analysis involving key stakeholders such as disaster management agencies, local government, and affected communities. The data were analysed using an interactive model to identify the strategic factors influencing HUNTARA development. The findings reveal that HUNTARA development in South Tapanuli is supported by strong internal factors, including regulatory backing, land availability, local architectural wisdom, and community participation. However, challenges remain, including limited budgets, inadequate skilled labour, infrastructure damage, and weak inter-agency coordination. External opportunities such as national rehabilitation programmes and improved construction technologies further enhance development potential. The SWOT analysis positions the programme in a growth-oriented strategy quadrant, indicating strong prospects for integrating temporary housing into long-term settlement renewal. In conclusion, HUNTARA serves not only as an emergency shelter solution but also as a strategic instrument for sustainable settlement rejuvenation. Future disaster recovery planning should strengthen institutional coordination, enhance spatial planning systems, and integrate community-based approaches to improve resilience and long-term sustainability.